How Do Emerging Countries Influence the Advertising World of Tomorrow? An Analysis of Last Year's Cannes International Festival of Creativity - Henrike Runge; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2012)
The Cannes Lions festival is one of the most important international indicators for professionals in the creative communications industry. Throughout the past few years there are a rising number of submissions and award winners coming from emerging and developing countries. This fact is surprising considering the background of relatively low local advertising budgets compared to industrialized nations. This article analyzes success factors and derives suggestions for the German marketing industry of how to benefit from them. – – Das internationale Werbefestival in Cannes ist einer der wichtigsten internationalen Gradmesser für kreative Werbung. In den letzten Jahren ist eine Zunahme sowohl an Einreichungen als auch an Gewinnern auszumachen, die ihren Ursprung in Schwellen- und Entwicklungsländern haben, was insbesondere unter dem Gesichtspunkt verwundert, dass die dortigen Werbebudgets im Vergleich zu den Budgets innerhalb den Ländern der ersten Welt in der Regel erheblich geringer ausfallen. Der vorliegende Artikel analysiert die Erfolgsfaktoren und leitet ab, wie sich diese durch die deutsche Marketingbranche nutzbar machen lassen.
Keywords: M37; M30; M3; 650; Werbefestival Cannes; Werbung; Cannes Festival; Advertising; Advertising Industry; Advertising Agency; Agencies; Communication; Awards; Creativity; Marketing; Marketing-Communications; Branding; Brand Management; Dienstleistung; Unternehmensdienstleistung; Werbewirkung; Werbung; Marketing; Marketingmanagement; Werbewirtschaft; Werbeforschung